Obstetric violence according to obstetric nurses - Michelle Gonçalves da Silva; Michelle Carreira Marcelino; Lívia Shélida Pinheiro Rodrigues; Rosário Carcaman Toro; Antonieta Keiko Kakuda Shimo (Universidade Federal do Ceará, 2014)
The objective was to report the experience of obstetric nurses on the obstetric violence experienced, witnessed and observed during their professional careers. This study is based on an account of experience of working in several health institutions such as basic health units, private and public hospitals, located in São Paulo, Brazil, in a period 5-36 years of technical training and professional experience from 1977 to 2013. The technique to expose the professional experiences was brainstorming. The results were divided into violent utterances of health professionals to patients, unnecessary and/or iatrogenic experiences procedures performed by health professionals and the institutional unpreparedness with unstructured environment. It is concluded that through the speeches of the obstetric nurses there are several obstetric violence experienced and witnessed in their work routines, with differences between two types of delivery care: evidence-based obstetrics and traditional care model.